(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article delves into the lexical semantic aspects of somatisms, exploring the cultural nuances embedded in bodily expressions in both English and Uzbek languages. The study employs a comprehensive methodology to analyze and compare these linguistic phenomena, shedding light on the subtle variations that reflect the unique cultural and social contexts of each language.